Effects of Digital Health Technology Literacy, Health Empowerment, and Self-efficacy on Health-promoting Behaviors among Adults in South Korea - Kim, Ji-Su; Kim, Hyejin; Shin, Hyerine; Chung, Yoongi (Journal of Posthumanism, 2025)
While previous research focused on digital device usage in eHealth services, this study examined the relationships between digital health technology literacy, health empowerment, and self-efficacy in predicting health-promoting behaviors. Participants (1086 adults) completed an online questionnaire. Descriptive statistics, t-tests, analyses of variance with Scheffé’s test, Pearson’s correlation coefficients, and multiple regression analyses were performed. Findings showed that age, economic status, religion, smoking, health empowerment, and self-efficacy affected health-promoting behaviors (35.6% explanatory power). However, digital health technology literacy was not a significant factor. Higher health empowerment and self-efficacy were associated with more health-promoting behaviors, with high economic status having the greatest influence. Factors influencing health-promoting behaviors did not differ significantly among the general adult population, individuals with specific diseases, or specific classes. Since digital health technology literacy did not significantly affect outcomes in the study population, further studies are needed on individuals with specific health conditions and the older adult population.